Estudo de eficiência energética do sistema de iluminação da associação beneficente Ouro Branco - (:unkn) unknown (Universidade Federal do Pampa, 2013)
This paper presents a study of energy efficiency in a health institution small. Seeks to determine the status of the lighting system of the institution anonymous, pointing to possible solutions to reduce electricity consumption. As a secondary objective this work also aims to adapt the facilities to standards in order to provide to patients and the healthcare staff welfare, comfort and quality service. The estimated potential electricity conservation is done by analyzing the technical and economic feasibility of lighting systems based on fluorescent lamps and LED tubular lamps. In order to verify the economic feasibility of implementation of an energy efficiency action determines some indicators, such as the return time of the retrofit and cost- benefit (RCB). Based on the methodology applied for the institution under study, there was the possibility of reduction of the equivalent of 57,30 MWh / year and avoided demand of 10,53 kW , representing a decrease of 45,34 % in energy consumption in the system lighting, which would result in a decrease in approximately 12,84 % of the energy bill of the establishment.
Keywords: Electrical engineering; Lighting; Energy efficiency; Electric power consumption; Engenharia elétrica; Eficiência energética; Iluminação; Consumo de energia elétrica; CNPQ::ENGENHARIAS